Possible regenerative effects of fingolimod (FTY720) in multiple sclerosis disease: An overview on remyelination process. Issue 3 (5th August 2019) - Yazdi, Azadeh; Ghasemi‐Kasman, Maryam; Javan, Mohammad
Abstract: Fingolimod (FTY720) is a sphingosine 1‐phosphate (S1P) receptor analog, which has been approved as an oral immunomodulator for treating relapsing–remitting multiple sclerosis. This drug prevents lymphocyte egression from lymph nodes and reduces the infiltration of inflammatory mediators into the central nervous system. Based on its lipophilic nature, FTY720 passes through the blood–brain barrier and can directly affect neural cells. A notably different subtype of S1P receptors expresses in neural cells, which suggests FTY720 is a drug capable of affecting neural cells. Oligodendrocytes (OLs) are considered as the primary target cells in MS. Remyelination is a process including the proliferation of neural progenitors and oligodendrocyte precursor cells, their migration to the lesion site and their differentiation to mature oligodendrocytes. Experimental and clinical studies have described the impact of FTY720 on endogenous remyelination elements. In this review, we will explain the current clinical and experimental evidence that exists on the effects of FTY720 on remyelination and the underlying mechanisms.